Comparing the case-mix of frail older people at home and of those being admitted into residential care: a longitudinal study - Johanna de Almeida Mello; Sophie Cès; Dirk Vanneste; Thérèse Van Durme; Chantal Van Audenhove; Jean Macq; Brant Fries; Anja Declercq (BMC Geriatrics, 2020)
Abstract Background In order to optimize interventions and services in the community, it is important to identify the profile of persons who are able to stay at home and of those who are being admitted into residential care. Understanding their needs and their use of resources is essential. The main objective of the study is to identify persons who are likely to enter residential care based upon their needs and resource utilization, so that care providers can plan interventions effectively and optimize services and resources to meet the persons’ needs. Methods This is a longitudinal quasi-experimental study. The data consists of primary data from the community setting collected every six months during the period of 2010–2016. Interventions had the goal of keeping older people longer at home. Participants were at least 65 years old and were living in the community. The interRAI Resource Utilization Group system (RUG-III) was used to calculate the case-mix indexes (CMI) of all participants. Comparisons were made between the case-mix of those who were still living at home and those who were admitted into residential care at follow-up. Results A total of 10,289 older persons participated in the study (81.2 ± 7.1 yrs., 69.1% female). From this population, 853 participants (8.3%) were admitted into residential care. The CMI of the persons receiving night care at home were the highest (1.6 at baseline and 1.7 at the entry point of residential care), followed by persons receiving occupational therapy (1.5 at baseline and 1.6 at the entry point of residential care) and persons enrolled in case management interventions with rehabilitation (1.4 at baseline and 1.6 at the entry point of residential care). The CMIs at follow-up were significantly higher than at baseline and the linear regression model showed that admission to residential care was a significant factor in the model. Conclusions The study showed that the RUG-III system offers possibilities for identifying persons at risk of institutionalization. Interventions designed to avoid early nursing home admission can make use of the RUG-III system to optimize care planning and the allocation of services and resources. Based on the RUG-III case-mix, resources can be allocated to keep older persons at home longer, bearing in mind the complexity of care and the availability of services in the community.